2017
DOI: 10.3389/fmicb.2017.01893
|View full text |Cite
|
Sign up to set email alerts
|

Caco-2 Invasion by Cronobacter sakazakii and Salmonella enterica Exposed to Drying and Heat Treatments in Dried State in Milk Powder

Abstract: Due to the ability of foodborne pathogens to survive in low moisture food, the decontamination of milk powder is an important issue in food protection. The safety of food products is, however, not always insured and the different steps in the processing of food involve physiological and metabolic changes in bacteria. Among these changes, virulence properties may also be affected. In this study, the effect of drying and successive thermal treatments on the invasion capacity of Salmonella Typhimurium, Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The Kdp system was shown to play a role in increasing the osmotolerance of Escherichia coli , Staphylococcus aureus and Sinorhizobium meliloti by allowing scavenging of K + when concentrations are low (Laimins et al, 1981; Gowrishankar, 1985; Domínguez-Ferreras et al, 2009; Price-Whelan et al, 2013). The genes kdpA , kdpB , and kdpC were found to be upregulated by 27-, 15-, and 8-fold, respectively, in Cronobacter sakazakii under osmotic stress (Lang et al, 2017). It is possible that the presence of this system in A. prosperus DSM 14174 renders this strain more resilient to salt stress than the other members of the genus when inhabiting K + limited environments.…”
Section: Resultsmentioning
confidence: 99%
“…The Kdp system was shown to play a role in increasing the osmotolerance of Escherichia coli , Staphylococcus aureus and Sinorhizobium meliloti by allowing scavenging of K + when concentrations are low (Laimins et al, 1981; Gowrishankar, 1985; Domínguez-Ferreras et al, 2009; Price-Whelan et al, 2013). The genes kdpA , kdpB , and kdpC were found to be upregulated by 27-, 15-, and 8-fold, respectively, in Cronobacter sakazakii under osmotic stress (Lang et al, 2017). It is possible that the presence of this system in A. prosperus DSM 14174 renders this strain more resilient to salt stress than the other members of the genus when inhabiting K + limited environments.…”
Section: Resultsmentioning
confidence: 99%
“…Typhimurium and S . Senftenberg cells [ 116 ], and the study by Yoon et al, (2013), who observed that exposure of S . Enteritidis cells to NaCl increased their cell invasion efficiency (Table 1) [ 117 ].…”
Section: Salmonella Stress Resistance Mechanismmentioning
confidence: 99%
“…The same authors reported that upon that heat shock the genes of two Salmonella pathogenicity islands (SPI-2 and SPI-5) were upregulated, which would explain their higher adhesion and would confer a higher chance of survival in the host while genes of SPI-1 were downregulated. In another study, Lang et al, 2017 compared the invasion ability of dried Salmonella cells after different heat treatments and likewise did not find any differences with the non-heat treated cells, although, in this case, the reduced metabolic activity of dried cells might explain the absence of effects of the heat treatment [ 116 ]. To the best of our knowledge there is only one work in which the virulence of stable variants/clones of Salmonella cells has been examined and the results of this work indicated that the heat resistant strain displayed a lower pathogenicity after intraperitoneal injections into 20–22 g mice [ 229 ].…”
Section: Salmonella Stress Resistance Mechanismmentioning
confidence: 99%
“…Most cases of C. sakazakii infection can be traced back to powdered infant formula (PIF), which often acts as the main source of infection [ 5 ]. Pasteurization, oligonutrition, low temperatures, or drying during the production and processing of PIF may induce C. sakazakii to enter a sublethal state, wherein it remains viable but cannot be cultured on a plate (VBNC) [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%